2020
DOI: 10.1021/acs.jafc.9b07819
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Glyphosate Residues in Foods from the Canadian Retail Markets between 2015 and 2017

Abstract: Underlying the risk management of pesticides to protect human health and to facilitate trade among nations are sound scientific data on the levels of compliance with standards set by governments and internationally from monitoring of the levels of pesticides in foods. Although glyphosate is among the universally used pesticides in the world, monitoring has been hampered by the analytical difficulties in dealing with this highly polar compound. Starting in 2015, using liquid chromatography/tandem mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…The predominance of glyphosate residues in the outer kernel layers is consistent with results from surveys of retail level wheat and wheat products (Granby et al., 2003; Kolakowski et al., 2020) as well as milling trials conducted in the mid‐1980s (Steinmetz, 1984; Steinmetz & Cowell, 1984). All wheat bran samples analyzed in the first two years of Granby et al .’s study contained measurable residues, while only about 60% of wheat grain and flour samples did.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The predominance of glyphosate residues in the outer kernel layers is consistent with results from surveys of retail level wheat and wheat products (Granby et al., 2003; Kolakowski et al., 2020) as well as milling trials conducted in the mid‐1980s (Steinmetz, 1984; Steinmetz & Cowell, 1984). All wheat bran samples analyzed in the first two years of Granby et al .’s study contained measurable residues, while only about 60% of wheat grain and flour samples did.…”
Section: Discussionsupporting
confidence: 79%
“…observed the highest concentration (8.5 mg/kg) in a survey of food items in a sample of wheat bran. They also reported that products made with whole wheat flour or wheat bran had higher concentrations of glyphosate than other products (Kolakowski et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the glyphosate residue levels summarized above for two major crops, soybean and maize, residue levels are available for other crops, including fruits, vegetables, and other grains, including regulatory agency surveys (EFSA, 2018(EFSA, , 2019(EFSA, , 2020Kolakowski et al, 2020;Zoller et al, 2018). An early government agency report about analyzing foods for glyphosate was conducted on samples collected in 2010 and 2012 in Germany (Scherbaum et al, 2012).…”
Section: Other Cropsmentioning
confidence: 99%
“…Glyphosate has not been found in milk, eggs, or fish from seven regulatory agency surveys, all of which used validated assays (EFSA, 2018(EFSA, , 2019(EFSA, , 2020FDA, 2018bFDA, , 2019Kolakowski et al, 2020;Zoller et al, 2018). One exception for the lack of glyphosate in animal products is that glyphosate was above the LOQ in three samples of sausage or meat loaf in the study of Zoller et al (2018), but there was no information about whether these samples were 100% meat or if they contained plant-based fillers.…”
Section: Animal Products (Milk Meat and Eggs)mentioning
confidence: 99%